Indian coalition politics: difficulties and consequences - Mohd Wani, Gull (International Journal of Psychosocial Rehabilitation, 2024)
How does governing in coalitions affect coalition parties’ responsiveness to voters? In this article, we seek to understand the relationship between political parties’ participation in multiparty governments and their responsiveness to voters. We argue that the extent to which coalition parties respond to policy priorities of voters is influenced by the divisiveness of policy issues within the cabinet and the ministerial responsibility for policies. To test our hypotheses, we combine data on the issue attention of 55 coalition parties from the Comparative Manifestos Project with data on government composition and data on the policy priorities of voters from the Comparative Study of Electoral Systems and various election studies in 45 elections across 16 European countries from 1972 to 2011. Any party may gain a majority in the lower house; if not, coalitions are formed by the political parties to gain a majority in the lower house for the formation of government. This research study will analyze the nature, challenges, and prospects of coalition governments in the Indian political process. The significance lies in the study of multi-party systems, the growth of regionalism, and its effect on the pattern of Centre-state relations. Further, there is failure of the national consensus on a parliamentary majority because for three decades the national government was headed by a coalition government or by a minority government from 1989 to 2014. From 1952 to 1977 and 1980 to 1989 was Congress dominance.